Proposta para elaboração de um vocabulário controlado em educação de surdos para o repositório Huet-Ines - Brasil - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2021)
The purpose of this paper is to report a proposal for the development of a controlled vocabulary in the education of the deaf to the Huet Repository of the National Institute of Education for the Deaf (INES). Controlled vocabulary plays an important role in a repository, as it is a tool that can represent the information contained in digital objects, allowing their recovery in a safe, efficient and effective way. Therefore, in this work, as a methodological procedure, a qualitative approach was adopted, characterized as a descriptive research and a case study. The results indicate how relevant is the existence of a controlled vocabulary on the topic of deaf education to enable better research conditions for users belonging to linguistic minorities who study, work or live in community with these minorities, as in the case of the Huet Repository.
Proposal for the preparation of a controlled vocabulary in deaf education for the Huet repository - Ines - Brazil
Keywords: Instituto Nacional de Educação de Surdos, Brasil; Repositório Huet; Vocabulário controlado; CNPQ::CIENCIAS SOCIAIS APLICADAS::COMUNICACAO